2016
DOI: 10.1002/jcu.22338
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability of emergency physician‐performed ultrasonography for diagnosing femoral, popliteal, and great saphenous vein thromboses compared to the criterion standard study by radiology

Abstract: Our study suggests that point-of-care sonography should not replace Radiology-performed scans. The required amount of training for EPs to be competent in this examination needs further investigation. © 2016 Wiley Periodicals, Inc. J Clin Ultrasound 44:360-367, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The main method of agreement when the gold standard is not available is Cohen’s Kappa. Only few studies in ED and ICU settings have reported Kappa statistics [ 20 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main method of agreement when the gold standard is not available is Cohen’s Kappa. Only few studies in ED and ICU settings have reported Kappa statistics [ 20 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The final research question and search strategy, PRISMA flow diagram, and results table of the final included studies are shown in tables Q6.1, Q6.2, and Q6.3, respectively. 23 references were presented 6 90 91 92 93 94 95 96 97 98 99 100 101 102 103 104 105 106 107 108 109 110 111 . The final summary of evidence, assignment of levels of evidence, and GRADE recommendation for this question are shown in table Q6.4.…”
Section: Resultsmentioning
confidence: 99%
“…If there was suspicion of pulmonary thromboembolism (PTE) with a dilated right ventricle, D-shaped left ventricle, or McConnell's sign on the cardiac view, a probe was used to perform the three-point compression technique for evaluation of DVT to determine the presence of uncompressible or limitedly compressible veins [8,9,14,15]. Although, evaluation of D-shaped left ventricle or McConnell's sign were difficult and not considered in emergencies.…”
Section: Methodsmentioning
confidence: 99%